2018
DOI: 10.7554/elife.32586
|View full text |Cite
|
Sign up to set email alerts
|

Crk proteins transduce FGF signaling to promote lens fiber cell elongation

Abstract: Specific cell shapes are fundamental to the organization and function of multicellular organisms. Fibroblast Growth Factor (FGF) signaling induces the elongation of lens fiber cells during vertebrate lens development. Nonetheless, exactly how this extracellular FGF signal is transmitted to the cytoskeletal network has previously not been determined. Here, we show that the Crk family of adaptor proteins, Crk and Crkl, are required for mouse lens morphogenesis but not differentiation. Genetic ablation and epista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…In contrast to the control lens that expressed PDGFRα in the anterior and Jag1 in the posterior, Frs2;Shp2 CKO mutants contained a hollow lens with only PDGFRα expression (Fig 7A, arrow and arrowheads). In a complementary approach, we also examined a transgenic mouse line ( Fgf3 OVE391 ) that overexpressed Fgf3 under control of an αA-crystallin promoter [46, 47]. As expected, pERK staining expanded from the transitional zone to the entire Fgf3 OVE391 lens, coinciding with ectopic induction of Jag1 and loss of PDGFRα expression in the anterior lens epithelium (Fig 7B, arrow and arrowheads).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast to the control lens that expressed PDGFRα in the anterior and Jag1 in the posterior, Frs2;Shp2 CKO mutants contained a hollow lens with only PDGFRα expression (Fig 7A, arrow and arrowheads). In a complementary approach, we also examined a transgenic mouse line ( Fgf3 OVE391 ) that overexpressed Fgf3 under control of an αA-crystallin promoter [46, 47]. As expected, pERK staining expanded from the transitional zone to the entire Fgf3 OVE391 lens, coinciding with ectopic induction of Jag1 and loss of PDGFRα expression in the anterior lens epithelium (Fig 7B, arrow and arrowheads).…”
Section: Resultsmentioning
confidence: 85%
“…First, despite their propensities to induce the same set of downstream signaling cascades, RTKs differ in their mode of engagement with these pathways. Whereas PDGFR directly binds the p85 subunit of PI3K to activate PI3K–AKT signaling, the main signaling output of FGFR is channeled through the adaptor protein Frs2, which recruits Shp2, Growth Factor Receptor Bound Protein 2 (Grb2), and v-crk avian sarcoma virus CT10 oncogene homolog (Crk) proteins to activate the Ras–MAPK signaling cascade [47, 63]. Although Grb2 has been reported to interact with GRB2-Associated Binding Protein 1 (Gab1) to activate PI3K, we previously showed that the genetic ablation of Gab1 and its homologue Gab2 failed to disrupt FGF signaling in both MEF cells and the developing lens [45, 64].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous neural-specific knockout of Crk and CrkL revealed essential overlapping roles downstream of Disabled-1 in the Reelin pathway regulating neuronal positioning (Park and Curran, 2008). Similar overlapping roles were seen in the kidney (George et al , 2014) and lens (Collins et al , 2018). However, to our knowledge, there has been no analysis of embryos lacking both Crk and CrkL from the onset of development.…”
Section: Introductionmentioning
confidence: 57%
“…Simultaneous neural-specific knockout of both Crk and CrkL revealed essential overlapping roles downstream of Disabled-1 in the Reelin pathway regulating neuronal positioning (Park and Curran, 2008). Similar overlapping roles were seen in the kidney (George et al, 2014) and lens (Collins et al, 2018). However, to our knowledge, there has been no analysis of mouse embryos lacking both CrkI/II and CrkL from the onset of development.…”
Section: Introductionmentioning
confidence: 90%